Pengaruh moralitas dan kepemimpinan kepala desa terhadap kepatuhan wajib pajak bumi dan bangunan - Sari, Widia Eka; Fahmi, Muhammad; Kusuma, Gumulya Sonny Marcel; Zuraidah, Ida (Owner : Riset dan Jurnal Akuntansi, 2024)
This study aims to determine the effect of the morality and leadership of the village head on the compliance of land and building tax payers in the village of Rimba Jaya, Air Kumbang District, Banyuasin Regency. The type of research used in this study was associative research. The research was conducted in the village of Rimba Jaya, Air Kumbang District, Banyuasin Regency. The population in this study were 956 taxpayers registered at Bapenda Banyuasin. The sampling technique used in this study was (simple random sampling). The data used are primary and secondary data. Data collection methods used were interviews and questionnaires. The data analysis method used in this research is quantitative analysis. The data analysis technique used in this research is validity test, reliability test, classical assumption test, coefficient of determination, multiple linear regression analysis, f test and t test. The results of this study simultaneously show that the morality and leadership of the village head have a significant effect on the compliance of land and building tax payers. Partially, morality has a significant effect on land and building tax payer compliance. Village head leadership does not have a significant effect on land and building tax payer compliance.